Remote Health Service Provision-Samsun Sample - Öz, Hatice (Turkey Health Literacy Journal, 2022)
Due to the content of the health service type of service, it is separated from other types of services. Recently, global events and technological developments have caused changes in service delivery. Remote health care has emerged as an opportunity in health service delivery. Within the scope of the pandemic process, the Ministry of Health announced the Tele-Health System in order to reduce the transmission and to reach the health services without threatening the public health of the risky people. It is aimed to develop this practice, which started in public hospitals, and family medicine practice processes from primary health care services. Samsun province was chosen as a pilot province for this application. Experiences have been made for those who benefit from health service provision in many areas such as conditions requiring special follow-up, chronic diseases, disabled and elderly individuals, and home health patients from this service. As a result, it is reported that the service can be used in the follow-up and follow-up of individuals, and at the same time, it will be more appropriate to use in operations such as proper nutrition, chronic wound care, increasing the use of breast milk, breastfeeding training, awareness in pregnant women, and counseling services to the relatives of bedridden patients at home.
Keywords: COVID-19, pandemic, patient, health, healthcare, technology